Population fluctuation in soil meso- and macrofauna by the successive application of pig slurry - da Silva, Rodrigo; Bertollo, Gilvan; Antoniolli, Zaida; Corassa, Geomar; Kuss, Cassiano (Revista Ciência Agronômica, 2016)
Pig farming has increased in recent years, resulting in the production of a large quantity of liquid manure, which can be used as a source of organic fertiliser. The aim of this work was to determine the influence of pig slurry on the community of soil fauna in a system of direct seeding. The study was carried out in an experimental area in the town of Taquaruçu do Sul, in the state of Rio Grande do Sul, Brazil. The experimental design was of randomised blocks in a (4 + 1) x 4 factorial scheme, comprising five fertilisation treatments, 0 (no fertiliser), 20, 40 and 80 m3 of pig slurry ha-1 and one additional treatment (mineral fertiliser), with four evaluations corresponding to the number of slurry application (1st, 2nd, 3rd and 4th application), and four replications. The soil fauna was sampled using PROVID traps. The following were evaluated: the relative frequency of the groups of soil fauna, the populations of springtails and mites, density, richness, Simpson’s dominance index and the Shannon diversity index. The populations of mites and springtails, and indices of diversity, richness and dominance are influenced by the successive application of pig slurry. Successive applications of pig slurry increase the diversity of the soil fauna by reducing the population of organisms of the Order Collembola. Canonical correlation analysis showed an association between the number of springtails and 80 m3 of pig slurry ha-1 after the third application.